Hubungan Usia Menarche dengan Depresi pada Remaja - Pertiwi, Annisa; Hafidh, Yulidar; Hikmayani, Nur Hafidha (Nexus Kedokteran Komunitas, 2014)
Background:Menarcheisone of the puberty signsin women.The timing of menarche had shifted towards earlier onset and the number ofyoung adolescent girlswho experiencedmenarcheearlier thantheir peers is increasing. Early menarche hadresulted in the acceleration of physical changes, but these are not always followed by emotional and psychological maturity, thereby causinga variety ofpsychologicalproblemssuch asdepression. This studyaimed to examinethe associationbetweenearlymenarcheand depression inadolescentgirls whileadjusting forother confounding variables(body massindex, economic status, andbirth order). Methods:This was ananalyticalobservationalstudy with cross-sectional approach. SubjectswereYear 8students atSMPNegeri 4 Surakarta. All subjects who met inclusion criteria were assessedfordepressionsymptoms using the Beck Depression Inventoryquestionnaire.Data on age at menarche, heightand weight,monthlyincome ofbothparents, andbirth order were collected.Data wereanalyzed by multivariatelogisticregression. Results: Of 111 participating subjects, 63,1% had experienced early menarche and 53,7% of whom had depression symptoms. In multivariate analysis, ageat menarchewas not statistically significantly associated with depression (OR=1.66;95% CI=0.716â3.863;p=0.237)after adjusting for body mass index and birth order. Conclusions:There was nosignificant associationbetweentiming ofmenarcheand depression inyoung adolescent girls after adjusting forbody mass index and birth order. Keywords:earlymenarche, depression, adolescent girls.Â